Student’s response to the integration of al-Qur’an values on the concept of quantities and units - Mohammad Djamil M Nur (Jurnal Pembelajaran Fisika, 2022)
The study aims to to determine the response of students to the integration of Al-Qur’an values in physics learning on the concept of quantities and units. This research is a survey study. Sampling was carried out using the Purposive Sampling method so that a sample of class X IPA4 was obtained because the class has been given physics learning of the concept of quantities and units by integrating the values of the Al-Qur’an.  Students' responses were measured using a questionnaire consisting of three aspects, namely spiritual attitudes, interests/ interests, and students' clarity/understanding of learning physics on the concept of quantities and units.  This research instrument is a response of students to the integration of Al-Qur’an values in learning physics of concept quantities and units with a percentage of 79.43%, showing very interesting results. Based on these findings, the integration of the value of the Al-Qur’an in the learning process can be used as an alternative in the physics learning process.Keywords: Quantities and units; integration of Al-Qur’an values; ResponseDOI: http://dx.doi.org/10.23960/jpf.v10.n2.202206